Tumour budding activity and cell nest size determine patient outcome in oral squamous cell carcinoma: proposal for an adjusted grading system - Boxberg, Melanie; Warth, Arne (Histopathology, 2017)
Aims Oral squamous cell carcinoma (OSCC) is a common malignancy with a variable clinical course. One of the established survival predictors in carcinomas in general is tumour grade; in OSCC, however, grading according to the World Health Organization (WHO) has no independent prognostic impact. Recently, a novel grading scheme associated with high impact on patient outcome has been proposed for squamous cell carcinoma of the lung. Methods and results To probe whether this scheme could be applied to the upper aerodigestive tract, we retrospectively evaluated 157 chemo- and radiotherapy-naive OSCCs with complete clinical follow-up data and standardized treatment for tumour budding activity (BA), cell nest size (CNS), extent of keratinization, stromal content, nuclear size and mitotic count. Histomorphological characteristics were correlated with clinicopathological data and patient outcome. As in squamous cell carcinoma of the lung, high BA and small CNS were correlated significantly with shortened overall, disease-specific and disease-free survival. A three-tiered grading system based on a sum score of these two prognostic markers proved to be a strong age-, stage- and sex-independent prognosticator for survival with a hazard ratio for overall survival of 2.1 for intermediately differentiated (G2) tumours and 3.4 for poorly differentiated (G3) tumours compared to well-differentiated (G1) tumours (P < 0.001). Conclusions We recapitulated and validated almost exactly the strong prognostic impact of a grading algorithm proposed recently for squamous cell carcinoma of the lung in OSCC. Our data may pave the way for a prognostically highly relevant future squamous cell carcinoma grading system broadly applicable in the aerodigestive tract.